Serum Nephrin Levels in Severe Preeclampsia: A Cross-Sectional Study : Kadar Nephrin Serum pada Preeklamsia Berat: Sebuah Studi Potong Lintang - Meice Fitrina; Sofie R. Krisnadi; Hartanto Bayuaji (Indonesian Journal of Obstetrics and Gynecology, 2021)
Abstract Objective: To determine differences in serum nephrin levels in severe preeclampsia compared to normal pregnancy and also its correlation with systolic and diastolic blood pressure and proteinuria.Methods: This study is an analytical observational with cross sectional study. The observation group consisted of severe preeclampsia (n= 30) and normal pregnancy group as a control (n= 30). Both groups measured systolic and diastolic blood pressure, proteinuria and serum nephrin using the Human NPHN (Nephrin) ELISA Kit. Statistical test were performed with Mann-Whitney test and the Spearman’s rank test. A value of p<0.05 was considered significant. The study was conducted in the Obstetric Clinic Inward and Laboratorium Department of Clinical Pathology Dr. Hasan Sadikin General Hospital/Faculty of Medicine Universitas Padjadjaran on March–May 2019.Results: Levels of serum nephrin in the severe preeclampsia group were significantly higher than in normal pregnancies (6.4 ng/mL vs 4.2 ng/mL; p= 0.014). There is a positive weak correlation but statistically significant between serum nephrin with systolic blood pressure (r= 0.36; p= 0.02) but not significant to diastolic blood pressure (r= 0.3; p= 0.05). There is no significant correlation was found between serum nephrin levels and proteinuria (r= 0.18; p= 0.54).Conlusions: Levels of serum nephrin in the severe preeclampsia group were significantly higher than in normal pregnancies and there is a correlation between serum nephrin with systolic blood pressure. Keywords: blood pressure, proteinuria, serum nephrin, podocyte, severe preeclampsia. Abstrak Tujuan: Untuk mengetahui perbedaan kadar nephrin serum pada preeklamsia berat dibandingkan dengan kehamilan normal dan juga hubungannya dengan tekanan darah sistolik dan diastolik serta proteinuria.Metode: Penelitian ini bersifat analitik observasional dengan pendekatan potong silang. Kelompok pengamatan terdiri dari kelompok preeklamsia berat (n= 30) dan kelompok kehamilan normal sebagai kontrol (n= 30). Pada kedua kelompok dilakukan pengukuran tekanan darah sistolik dan diastolik, proteinuria serta pengukuran kadar nephrin serum menggunakan Human NPHN (Nephrin) ELISA Kit. Uji statistik dilakukan dengan uji Mann-Whitney dan uji rank Spearman. Nilai p<0,05 dianggap bermakna. Penelitian dilakukan di ruang perawatan obstetri FKUP/RSHS dan Laboratorium Patologi Klinik FKUP/RSHS pada bulan Maret-Mei 2019.Hasil: Rerata kadar nephrin serum pada kelompok preeklamsia berat lebih tinggi secara bermakna dibandingkan kehamilan normal (6,4 ng/mL vs 4,2 ng/mL; p= 0,014). Terdapat korelasi positif dengan derajat lemah namun bermakna secara statistik antara nephrin serum dengan tekanan darah sistolik (r= 0,36; p= 0,02) namun tidak signifikan terhadap tekanan darah diastolik (r= 0,3; p= 0,05). Tidak ditemukan korelasi yang bermakna antara kadar nephrin serum dengan proteinuria (r= 0,18; p= 0,54). Kesimpulan: Kadar nephrin serum pada kelompok preeklamsia berat lebih tinggi dibandingkan kehamilan normal dan terdapat korelasi antara nephrin serum dengan tekanan darah sistolik. Kata kunci: nephrin serum, podosit, preeklamsia berat, proteinuria, tekanan darah